Pneumoperitoneum simulation based on mass-spring-damper models for laparoscopic surgical planning - Nimura, Yukitaka (J Med Imaging (Bellingham), 2015)
Laparoscopic surgery, which is one minimally invasive surgical technique that is now widely performed, is done by making a working space (pneumoperitoneum) by infusing carbon dioxide ([Formula: see text]) gas into the abdominal cavity. A virtual pneumoperitoneum method that simulates the abdominal wall and viscera motion by the pneumoperitoneum based on mass-spring-damper models (MSDMs) with mechanical properties is proposed. Our proposed method simulates the pneumoperitoneum based on MSDMs and Newton’s equations of motion. The parameters of MSDMs are determined by the anatomical knowledge of the mechanical properties of human tissues. Virtual [Formula: see text] gas pressure is applied to the boundary surface of the abdominal cavity. The abdominal shapes after creation of the pneumoperitoneum are computed by solving the equations of motion. The mean position errors of our proposed method using 10 mmHg virtual gas pressure were [Formula: see text] , and the position error of the previous method proposed by Kitasaka et al. was 35.6 mm. The differences in the errors were statistically significant ([Formula: see text] , Student’s [Formula: see text]-test). The position error of the proposed method was reduced from [Formula: see text] to [Formula: see text] using 30 mmHg virtual gas pressure. The proposed method simulated abdominal wall motion by infused gas pressure and generated deformed volumetric images from a preoperative volumetric image. Our method predicted abdominal wall deformation by just giving the [Formula: see text] gas pressure and the tissue properties. Measurement of the visceral displacement will be required to validate the visceral motion.